Oral Rehabilitation of Parkinson’s Disease Patient: A Review and Case Report - Fouad A. Al-Omari; Mohammed M. Al Moaleem; Sulaiman S. Al-Qahtani; Abdullah S. Al Garni; Syed Sadatullah; Master Luqman (Case Reports in Dentistry)
Parkinson’s disease is usually seen in adults in their middle and late ages. Most people with this disease are less likely to opt for dental treatments unless it is an acute condition. Tremors caused by Parkinson’s disease can make dental appointments, especially prolonged treatments, a challenge. The case presented here was successfully treated with an immediate denture for the partially edentulous maxillary and mandibular arches. Early morning brief appointments were given for the procedure. Patient was instructed to take the prescribed parkinsonism medications 60 to 90 minutes before the appointment to utilize the advantage of its peak response. Sympathetic and caring approach towards the patient was employed to reduce his anxiety during the procedures. Some modification of technics and materials was adopted to suit the special situation.